2020
DOI: 10.1093/zoolinnean/zlaa132
|View full text |Cite
|
Sign up to set email alerts
|

Going underwater: multiple origins and functional morphology of piercing-sucking feeding and tracheal system adaptations in water scavenger beetle larvae (Coleoptera: Hydrophiloidea)

Abstract: Larvae of water scavenger beetles (Coleoptera: Hydrophiloidea) are adapted to a wide variety of aquatic habitats, but little is known about functional and evolutionary aspects of these adaptations. We review the functional morphology and evolution of feeding strategies of larvae of the families Hydrophilidae and Epimetopidae based on a detailed scanning electron microscope (SEM) analysis, analysis of video records of feeding behaviour and observations of living larvae. There are two main types of feeding mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…2018; Rodriguez et al . 2020). These ‘specialized’ larvae are presumed to have evolved for a benthic way of life independently within the family Hydrophilidae (Rodriguez et al .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…2018; Rodriguez et al . 2020). These ‘specialized’ larvae are presumed to have evolved for a benthic way of life independently within the family Hydrophilidae (Rodriguez et al .…”
Section: Figurementioning
confidence: 99%
“…These ‘specialized’ larvae are presumed to have evolved for a benthic way of life independently within the family Hydrophilidae (Rodriguez et al . 2020). The Hydrochidae larvae, as described by Richmond (1920) and Archangelsky (1997), have large, open respiratory organs in the abdomen, suggesting that they breathe on the surface of the water; however, in reality, they remain in the water and do not come to the surface.…”
Section: Figurementioning
confidence: 99%
“…In recent years, the evolution of adult and larval morphology in Hydrophilidae has been studied (Short & Fikáček 2013; Rodriguez et al . 2020), but the pupae have not been thoroughly investigated.…”
Section: Figurementioning
confidence: 99%
“…Pupae of this species are thought to have evolved to breathe in water, and detailed observations of their morphology and respiratory organs will contribute to the study of the evolution of the Hydrophilidae. In recent years, the evolution of adult and larval morphology in Hydrophilidae has been studied (Short & Fik ac ˇek 2013;Rodriguez et al 2020), but the pupae have not been thoroughly investigated.…”
mentioning
confidence: 99%
“…For example, some studies have shown that mammal and fish feeding ecology has a stronger evolutionary influence on functional morphology [2,3]. There are a small but increasing number of functional studies exploring the relationship between morphology and feeding ecology in invertebrates, mainly in arachnids and insects [4][5][6][7][8]. A few studies have shown that some parameters,including shape and force, play a key role in prey capture in some predators.…”
Section: Introductionmentioning
confidence: 99%